Performance of the TRUE dilatation balloon valvuloplasty catheter beyond rated burst pressure: A bench study. Issue 2 (30th September 2019) - Sathananthan, Janarthanan; Hensey, Mark; Sellers, Stephanie; Barlow, Aaron M.; Chhatriwalla, Adnan K.; Allen, Keith B.; Cheung, Anson; Søndergaard, Lars; Blanke, Philipp; Ye, Jian; Leipsic, Jonathan; Wood, David; et al.
Abstract : Objectives: We undertook an independent bench test assessing the performance of the TRUE dilatation (TD) balloon valvuloplasty catheter (Bard Vascular Inc., Tempe, AZ) beyond its rated burst pressure (RBP). Background: The TD balloon has a RBP of six atmospheres (atm), and its performance beyond this RBP is poorly understood. Techniques such as bioprosthetic valve fracture require inflation pressures beyond manufacturer recommendations. Methods: A 20, 22, 24, 26, and 28 mm TD balloon were inflated to increasing pressures in increments of 3 atm until balloon failure. Measurements were performed at the proximal, middle, and distal balloon segments with scientific digital calipers. Z‐MED balloons (Braun Interventional Systems Inc., Bethlehem, PA) were used as a comparator. Results: The mean diameter at the middle of the 20, 22, 24, 26, and 28 mm TD balloon at nominal pressure (3 atm) was 20.02 ± 0.09, 21.77 ± 0.07, 23.9 ± 0.06, 25.82 ± 0.08, and 27.62 ± 0.08 mm, respectively. The maximal mean diameter at the middle of the 20, 22, 24, 26, and 28 mm TD balloon was 20.39 ± 0.03 mm (15 atm), 22.35 ± 0.03 mm (15 atm), 24.55 ± 0.02 mm (15 atm), 26.48 ± 0.02 mm (12 atm), and 28.39 ± 0.03 mm (12 atm), respectively. The 20/22/24 and 26/28 mm balloon failed when inflated beyond 15 atm and 12 atm, respectively. Failure was due to either leakage or longitudinal balloon rupture. TD balloons were more likely to maintain dimensions similar to their labeled size and less likely to fail at higher pressures as compared to Z‐MED balloons. Conclusion: The TD balloon catheter maintains a similar diameter to its labeled size, when inflated beyond its RBP. When inflated beyond 12 atm, the TD balloon can fail due to either leakage or rupture. This has implications for percutaneous structural heart interventions.